Evaluation of food photographs assessing the dietary intake of children up to 10 years old - Valanou, Elisavet; Naska, Androniki; Barbouni, Anastasia; Katsoulis, Michael; Peppa, Eleni; Vidalis, Pavlos; Trichopoulou, Antonia (Public health nutrition, 2018)
Young children lack basic skills related to recognizing the types of foods they consume and dietary surveys often rely on parents' response. The present study aimed to evaluate how well parents of children aged from 3 months to 10 years perceive images of portions of foods commonly consumed by young children. Pre-weighed, actual food portions (n 2314) were shown to the study participants who were asked to indicate the picture that corresponded to the food in view. Mean differences between picture numbers selected and shown were estimated and compared using unpaired t tests or Tukey-Cramer pairwise comparisons. Real-time testing of parents' perception of food images presenting portion sizes consumed by children up to 10 years old. A convenience sample of 138 parents/caregivers of young children (69 % females). Individuals selected the correct or adjacent image in about 97 % of the assessments. Images presenting amorphous solids (i.e. pies and pastries with a filling), liquid or semi-liquid dishes (i.e. soups, porridges, fruit and vegetable purées) were more prone to bias. There was no indication that personal characteristics (gender, age, educational background, age, number of offspring) were associated with differences in the way parents/caregivers perceived the food pictures. Food pictures may not be appropriate to quantify the intake of liquid, semi-liquid or amorphous solid foods in surveys addressing young children and studies evaluating their performance as food portion anchors should ensure the inclusion of several and various amorphous foods in the assessment.